The Influence of Religiosity on Self-Control among Out of Town Students in Pontianak - Audina, Mira; Risna Hayati; Riszky Ramadhan (The Future of Education Journal, 2025)
Students who live away from home or are separated from their parents often face difficulties in self-control. The contributing factors include themselves, their living environment (boarding houses), academic surroundings, social interactions, peer groups, and religiosity, which can also influence self-control. Students who lack religious guidance and direction in their lives may experience behaviors that deviate from religious teachings, leading to actions that are prohibited by their religion. The purpose of this study is to provide factual data to demonstrate the influence of religiosity on self-control among out-of-town students in Pontianak. The research method used is quantitative, with purposive sampling as the sampling technique. The subjects of this study consisted of 100 out-of-town students in Pontianak. Data analysis was conducted using simple linear regression analysis with the IBM SPSS Statistics v.25 program. The results showed a regression coefficient of 0.030 with a significance value of 0.03<0.05, indicating a positive influence on self-control. Religiosity contributes 7.9% effectively to self-control, while the remaining 92.1% is influenced by other factors not explored in this study.